PERAN LEMBAGA KEUANGAN MIKRO DALAM MENINGKATKAN AKSES PEMBIAYAAN USAHA KECIL DI KOTA MEDAN - Maharani, Nurul Sandra; Harahap, Sri Widya; Salsabilla, Salsabilla; Yumna, Afrian Andika; Hayati, Fitri (LP2M Universitas Bina Bangsa, 2025)
Microfinance Institutions (MFIs) have a strategic role in improving access to finance for small businesses in Medan City, Indonesia. This study aims to analyze the contribution of MFIs in providing more inclusive and flexible financing solutions for small businesses that are often marginalized from the formal banking system. Methods This study uses a qualitative approach with a literature study to analyze the role of microfinance institutions in improving access to financing for small businesses in Medan City. The results show that MFIs not only offer convenience in the loan application process, but also provide essential training and mentoring to improve the capacity and competitiveness of small businesses. MFIs contribute significantly to local economic growth, challenges such as lack of community understanding of MFI products and limited resources still need to be addressed. This study recommends the need for support from the government and other stakeholders to strengthen the role of MFIs in supporting small businesses. With the right strategy, MFIs can continue to contribute to community economic empowerment and create positive social impact.